2002
DOI: 10.1007/s00484-002-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extremely hot days on people older than 65 years in Seville (Spain) from 1986 to 1997

Abstract: The effects of heat waves on the population have been described by different authors and a consistent relationship between mortality and temperature has been found, especially in elderly subjects. The present paper studies this effect in Seville, a city in the south of Spain, known for its climate of mild winters and hot summers, when the temperature frequently exceeds 40 degrees C. This study focuses on the summer months (June to September) for the years from 1986 to 1997. The relationships between total dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…The fact that the excess mortality due to heat is more pronounced in females than males is in accord with western European countries during the 2003 heat waves (e.g., Pirard et al 2005;Michelozzi et al 2005;Borrell et al 2006) as well as other previous events (Rooney et al 1998;Díaz et al 2002aDíaz et al , 2002b. It is likely related to a demographic and social structure of the European population, particularly a larger percentage of females among the elderly and among those living alone (INSTRAW 2004).…”
Section: Enhanced Mortality Impacts In Femalesmentioning
confidence: 84%
See 2 more Smart Citations
“…The fact that the excess mortality due to heat is more pronounced in females than males is in accord with western European countries during the 2003 heat waves (e.g., Pirard et al 2005;Michelozzi et al 2005;Borrell et al 2006) as well as other previous events (Rooney et al 1998;Díaz et al 2002aDíaz et al , 2002b. It is likely related to a demographic and social structure of the European population, particularly a larger percentage of females among the elderly and among those living alone (INSTRAW 2004).…”
Section: Enhanced Mortality Impacts In Femalesmentioning
confidence: 84%
“…Since the relationship between summer heat and mortality is often found to be stronger with the lag of 1 day compared to unlagged relationships (Auliciems et al 1997, Díaz et al 2002a, Ramlow and Kuller 1990, Sartor et al 1995, Whitman et al 1997, Davis et al 2003, Grize et al 2005, Kosatsky 2005), both the 0-day and 1-day lags between mortality and HI were examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that women are more vulnerable to heat-related mortality than men [22], [23], [24], [25]. Studies have also found that women have higher risks for ischemic, arrhythmic and blood pressure effects associated with the weather [26], [27]. However, Basu [28] pointed out that the differences of the effect of temperature on women and men was dependent on location and population.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum temperature was chosen as the index providing best fit in previous single city-studies conducted in Spain cities [13-15]. A lagged effect for up to two days, after that heat effects declined has also been shown [12].…”
Section: Methodsmentioning
confidence: 99%